The Effect of Administration of Lycopene on Interleukin 8 Levels and Hospitalization Time of Patients with Chronic Obstructive Pulmonary Disease Exacerbations - Yusup Subagio Sutanto; Diana Kurniasari Sagita; Suradi Suradi; Hendra Kurniawan (Jurnal Kedokteran Syiah Kuala, 2020)
Background: Exacerbated chronic obstructive pulmonary disease is an acute condition, characterized by persistent air flow limitations, related to the excessive chronic inflammatory response in the airways and lung parenchyma caused by exposure to harmful gases or particles. Increased airway inflammation during exacerbations leads to increased levels of IL-8 and the risk of hospitalization. Lycopene is a carotenoid which has a positive effect on the respiratory system. The purpose of this study was to determine the effect of administration  lycopene to IL-8 levels and hospitalization time of patients with COPD disease exacerbations.Methods: The  experimental test with pretest and posttest  design for 30 patients with COPD exacerbations in Dr. Moewardi Surakarta Hospital and Dr. Soehadi Prijonegoro Sragen Hospital was conducted from February to March 2018. Samples were taken by consecutive sampling divided into two groups including the treatment group receiving standard therapy and lycopene 1x10 mg / day during treatment and the control group only receiving standard therapy. IL-8 levels  and hospitalization time of patients with COPD disease exacerbations  were measured.Results: There were significant differences between the treatment group compared to the control group for a decrease in IL-8 (p = 0.029) and a decrease in hospitalization time (p = 0,000).Conclusion: The administration of lycopene 1x10 mg / day significantly reduce IL-8 levels and hospitalization time of patient with COPD exacerbations.